ABCA4 c.6480-35A>G, a novel branchpoint variant associated with Stargardt disease - Rodríguez-Hidalgo, María; de Bruijn, Suzanne E.; Corradi, Zelia; Rodenburg, Kim; Lara-López, Araceli; Valverde-Megías, Alicia; Ávila-Fernández, Almudena; Fernandez-Caballero, Lidia; Del Pozo-Valero, Marta; Corominas, Jordi; Gilissen, Christian; Irigoyen, Cristina; et al. (Frontiers in Genetics, 2023)
Inherited retinal dystrophies (IRDs) can be caused by variants in more than 280 genes. The ATPbinding cassette transporter type A4 (ABCA4) gene is one of these genes and has been linked to Stargardt disease type 1 (STGD1), fundus flavimaculatus, cone-rod dystrophy (CRD), and pan-retinal CRD. Approximately 25% of ABCA4 reported variants affect RNA splicing. In most cases it is necessary to perform a functional assay to determine the effect of these variants. Through the analysis of WGS data from a cohort of 69 cases, we identified two candidate variants in ABCA4 in one proband. A previously described deletion, c.699_768+342del (p.(Gln234Phefs*5)), and a novel branchpoint variant, c.6480-35A>G. Segregation analysis confirmed that the variants were in trans. For the branchpoint variant, SpliceAI predicted an acceptor gain with a high score (0.47) at the position c.6480-47. Midigene splice assay in HEK293T cells revealed the inclusion of the last 47 nucleotides of intron 47 creating a premature stop codon and allowed to categorize the variant as moderately severe. Subsequent analysis revealed the presence of this variant as a second allele besides c.1958G>A p.(Arg653His) in an additional Spanish proband in a large cohort of IRD-cases. A splice-altering effect of the branchpoint variant, confirmed by midigene splice assay, along with the identification of this variant in a second unrelated individual affected with STGD, provides sufficient evidence to classify the variant as likely pathogenic. In addition, this research highlights the importance of studying noncoding regions and performing functional assays to provide a conclusive molecular diagnosis.